Cultivo de girassol no município de Capitão Poço - PA: plastocrono, lâminas de água e adubação borácica - Silva, Raimundo Thiago Lima da (2015)
The obtainment of information through the research has been decisive to provide technological support to sunflowers culture development, granting better productivities and economical incomes. Among the various technologies developed to sunflowers production, the adequate choice of cultivars constitutes one of the main components in the system of culture production. Considering the existence of the interaction genotypes x environment, researches are required, aiming to determine the agronomic behavior of genotypes and their adaptation to different environment conditions. Based on these principles, there were developed four experiments in Capitão Poço City, in Pará State, in Brazil, with two sunflower cultivars, Embrapa – 122 and Catissol. On experiment I, sunflower cultivars’ plastochron was determined, sowed in two seasons in the year. On experiment II, the effect of different water slides over the productive behavior of sunflower cultivars was evaluated, which were cultivated in protected behavior, aiming to define criteria to irrigation handling. On experiment III, there were evaluated seven doses of boron (10 mg, 20 mg, 30 mg, 40 mg, 50 mg, 60 mg, 70 mg plant-1) and a witness, on the growing characteristics and on sunflower plants production. And on Experiment IV, the objective was to verify the relative content of water, the concentrations of total soluble amino acids, of total soluble proteins, of free ammoniums, deprolina and the activity of nitrate reductase, in sunflower leaves, in function of two cultivars and of different water slides. Through the obtained results, it was concluded that: the sowing seasons, the sub periods of vegetative development and the cultivars, possess different rights over the plastochron in sunflowers, with variations of 14,6 to 8787,0 °C day knot-1; the cultivar Catissol obtained values of mass of dried matter from the aerial part, mass of dried matter from the flower and the flower diameter responded in a linear way to the water slides. The variables, production, mass of 100 achenes and the number of leaves, were optimized by small doses of boron; and, finally, the applied water slides influenced on the concentrations of amino acids, protein, proline, relative content of water and on the activity of nitrate reductase, on sunflower leaves, as the genetic material in studies, presented different results, to these variables, excepting for the activity of nitrate reductase. Therefore, it was realized that sunflowers make mechanisms of osmotic adjustment in leaves, to tolerate various situations of humidity of water in the soil.